STRATEGI PENGELOLAAN ANGKUTAN KOTA (ANGKOT) DI KOTA MAGELANG MELALUI ANALISIS SWOT - Atmojo, Wijoseno Cahyo; Sudjatmiko, Sudjatmiko; Mukti, Ari (Jendela Inovasi Daerah, 2025)
Transportation problems in Magelang City are characterized by a decline in public interest in using city public transportation (angkot), which has an impact on reducing the number of public transportation and decreasing the income of drivers. On the other hand, the budget allocated by the Magelang City Transportation Service has not been able to encourage the modernization of city transportation management. This research aims to formulate a strategic planning model in managing public transportation in Magelang City. The method used is descriptive qualitative with a SWOT analysis approach. Data collection techniques are carried out through observation, interviews and documentation. The data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The research results show that there are seven aspects in the strength dimension, four aspects in the weakness dimension, four aspects in the opportunity dimension, and five aspects in the threat dimension. Based on the results of the SWOT analysis, 14 strategic planning points were formulated which can be used as a reference by stakeholders in efforts to develop and manage public transportation in Magelang City more effectively and sustainably.